Chemical composition and fatty acid profile of the longissimus dorsi muscle in Simmental bulls. (September 2019) - Lukic, M; Trbovic, D; Petronijevic, R; Djordjevic, V; Karan, D; Babic Milijasevic, J; Petrovic, Z
Abstract: The aim of this paper was to evaluate the carcass traits (live weight at slaughter, hot and cold carcass weights, dressing percentage, chilling loss), chemical composition and fatty acid profile of longissimus dorsi muscle (MLD) of Simmental bulls. The investigation was carried out on 10 Simmental bulls fattened in intensive conditions. The live, hot and cold carcass weights at slaughter were 597.9±29.53 kg, 326.9±17.06 kg and 319.4±16.64 kg, respectively. Dressing percentage was 54.6±1.17% and chilling loss was 2.3±0.26%. The mean muscle chemical composition was: dry matter 24.14 ±0.19%, water 75.86 ±0.59%, protein 20.78 ±0.30%, intramuscular fat 2.35 ±0.39%, ash 1.01±0.05%. High correlation was detected between live weight, hot carcass weight and cold carcass weight. The fatty acids of intramuscular fat consisted of 48.02±0.99%, 46.47±1.30% and 5.51±0.28% saturated (SFA), monounsaturated (MUFA) and polyunsaturated fatty acids (PUFA), respectively. The PUFA/SFA ratio was low (around 0.1), but the n-6/n-3 PUFA ratio was 4.24 and close to the recommended value. The level of MUFA correlated highly with the Δ9-desaturase (18) index (r=0.82 p<0.05) and oleic acid (C18:1n-9) (r=0.90 p<0.05), as did PUFA and linoleic acid (C18:2n-6) (r=0.96 p<0.05). Correlations (p<0.05), between major fatty acids, live weight and intramuscular fat were weak.